FIE'99 Frontiers in Education. 29th Annual Frontiers in Education Conference. Designing the Future of Science and Engineering E
DOI: 10.1109/fie.1999.841712
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cyber-learning

Abstract: Classroom instructions have been an old method of teaching-learning process. In a typical lecture referring back to some established entity, idea or theory often leaves the student in a dificulty, yearning for the refresher of the basics.Essential time constraint, confinement of basic ideas and lack of interactive training aids make it cumbersome for students to cope up with new ideas being taught. Cyber Learning is relatively a new concept, involving on-line teacher-student interaction, information from relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Some found that students were satisfied in general [4]. Students reported higher levels of subjective satisfaction with e-learning than with the traditional classroom learning [20].…”
Section: Development Of Hypothesesmentioning
confidence: 96%
“…Some found that students were satisfied in general [4]. Students reported higher levels of subjective satisfaction with e-learning than with the traditional classroom learning [20].…”
Section: Development Of Hypothesesmentioning
confidence: 96%
“…Extensive research has shown that in contrast to traditional classroom learning, e-learning has several advantages for learners [10,11,12]. Many studies have reported that e-learning is at least as effective as traditional classroom learning, measured by exam grades and learner's satisfaction [10,13]. While most literature emphasizes the benefits of e-learning, some researchers have also pointed out its drawbacks such as frustration, confusion, and a reduced interest in subject matters [14].…”
Section: Asynchronous E-learning Systemmentioning
confidence: 99%
“…For example, previous studies in e-learning and work carried out in [9,13] reported that students are less satisfied with the use of a technology in learning due to them already being accustomed to their traditional ways or experiencing frustration or worry during online learning. On the other hand, other studies as in [16,6] found a higher level of subjective satisfaction from students with a new e-learning tool compared to the traditional classroom learning.…”
Section: Discussionmentioning
confidence: 76%